Quality of Life after Staged Revision for Infected Total Hip Arthroplasty: A Systematic Review. Issue 4 (25th July 2016) - Rietbergen, Luuk; Kuiper, Jesse W.P.; Walgrave, Simon; Hak, Laura; Colen, Sascha
Introduction: The aim of this review was to assess (health-related) quality of life ([HR]Qol) after 1-stage or 2-stage revision for prosthetic joint infection of the hip (PJI). Additionally, we compared (HR)QoL scores with normative population scores to assess whether QoL is reduced after revision for PJI. Methods: A systematic search was performed in Embase, Cochrane and Pubmed. We included articles that reported (HR)QoL questionnaires after staged revision for hip PJI with a minimum follow-up of 24 months. Methodological quality was assessed using the MINORS score. Results: The search produced 11, 195 results. We selected 12 papers describing 2-stage revisions. The mean MINORS score was 9.8. Average WOMAC scores of 185 patients with a mean follow-up of 69.8 months were 73. Average Short Form 36 (SF-36) scores of 159 patients with a mean follow-up of 40.7 months were 40.4 for the physical component score (PCS) and 51.6 for the mental component score (MCS). Average Short Form 12 (SF-12) scores of 154 patients with a mean follow-up of 73.4 months were: a PCS of 35.4 and a MCS of 49.1. The WOMAC, SF-12 (PCS) and SF-36 (PCS) were respectively 12%, 26.7% and 14.8% lower, compared to normative values. Discussions: Patients who underwent 2-stage revision for hip PJI had substantially lower (physical component) (HR)QoL scores, but mental scores were comparable to the general population.